2021
DOI: 10.3390/s21051784
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Research Solutions to Manage Obstructive Sleep Apnea: A Review

Abstract: Obstructive sleep apnea (OSA), a common sleep disorder disease, affects millions of people. Without appropriate treatment, this disease can provoke several health-related risks including stroke and sudden death. A variety of treatments have been introduced to relieve OSA. The main present clinical treatments and undertaken research activities to improve the success rate of OSA were covered in this paper. Additionally, guidelines on choosing a suitable treatment based on scientific evidence and objective compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 125 publications
(148 reference statements)
0
17
0
6
Order By: Relevance
“…This obstruction is a life-threatening disease that needs consistent assessment and either non-invasive or different invasive intervention methods [ 19 ]. Among a series of methods to treat upper airway obstruction, electrical stimulation shows a potential high-performance solution [ 20 ]. The principle of an electrical stimulation system is to treat upper airway obstruction since the genioglossal muscle can be contracted when stimulating the hypoglossal nerve.…”
Section: Proposed System Modulesmentioning
confidence: 99%
“…This obstruction is a life-threatening disease that needs consistent assessment and either non-invasive or different invasive intervention methods [ 19 ]. Among a series of methods to treat upper airway obstruction, electrical stimulation shows a potential high-performance solution [ 20 ]. The principle of an electrical stimulation system is to treat upper airway obstruction since the genioglossal muscle can be contracted when stimulating the hypoglossal nerve.…”
Section: Proposed System Modulesmentioning
confidence: 99%
“…This obstruction is a life-threatening disease which needs consistent assessment and either non-invasive or different invasive intervention methods [14]. Among series of methods to treat upper airway obstruction, electrical stimulation show potential high-performance solution [15]. The principle of electrical stimulation system to treat upper airway obstruction since the genioglossal muscle can be contracted when stimulating the hypoglossal nerve.…”
Section: Respiration Monitoring and Electrical/magnetic Stimulationmentioning
confidence: 99%
“…In 2016, the first case of HNS for OSA in adolescents with DS was reported ( 15 ). Although most research in recent years have shown that HNS is a better option, these studies have limitations in terms of sample size, in follow-up duration, and in documentation of complications ( 16 ).…”
Section: Introductionmentioning
confidence: 99%